Stem CEOs and financial distress: An analysis of leadership, innovation, and risk in corporate financial performance - Harymawan, Iman; Novita, Santi; Habiburrochman; Prasetya, Fandi; Ulufiyah, Rosyadatul (International Journal of Management and Sustainability, 2025)
This paper examines whether CEOs with STEM backgrounds have a relationship with corporate financial distress, using 2022 data from Sustainalytics ESG Risk Ratings. Our findings reveal that companies led by STEM CEOs exhibit a statistically higher Altman Z-Scores, indicating a lower risk of financial distress. It shows that STEM CEOs contribute to financial resilience through structured innovation, operational efficiency, and disciplined investment strategies because of their analytical minds and long-term orientation. The study finds that STEM CEOs are more likely to adopt data-driven and future-driven decision-making frameworks, which help maintain financial stability even in volatile markets. Our heterogeneity analysis reveals that the positive impact of STEM leadership is more significant among firms in developed countries, firms led by male CEOs, smaller firms, firms with smaller boards, and firms with lower levels of innovation. These results are robust to multiple tests, including Coarsened Exact Matching (CEM), Propensity Score Matching (PSM), and Two-Stage Least Squares (2SLS) instrumental variable regression. This study contributes to the leadership and corporate finance literature by showing how a STEM CEO’s educational background can impact firm-level financial outcomes. The findings also offer practical implications for corporate governance, talent selection, and policy interventions to promote financial resilience through STEM leadership.